El impacto de la pobreza en la tasa de homicidios: un estudio econométrico en América Latina durante el período 2005-2020 - Valdiviezo Cumbicus, Jostin Jampier (2023)
Homicides in Latin America in 2019 reached a rate of 24.6 per 100,000 inhabitants, proclaiming itself as the most violent region globally. Therefore, the present research has as its main objective; to analyze the impact of poverty on the homicide rate in Latin America, during the period 2005-2020, using statistical and econometric methods in order to propose policies aimed at reducing social insecurity in the region. Consequently, data have been collected from the World Bank [WB], the Index of Globalization [KOF] and Transparency International [TI]. It should be noted that the data were collected in the year 2023 for subsequent use with a panel data methodology. As a result of the research, it was found that poverty and corruption have a positive relationship with homicides and also a positive relationship in the long term, while unemployment did not show statistical significance, except in lower middle-income countries, where it was found to have a positive relationship. The opposite is true for globalization, with an inverse relationship, which could be interpreted as a possible solution to the problem. In this way, it is recommended that government policy implications focus on improving the living conditions of low-income people in order to avoid recruitment by criminal groups. In addition, programs are proposed to reintegrate people who have been deprived of their liberty into society, thus preventing them from committing acts against society.